Clinical Profile, Radiological Findings, and Risk Factors Associated with Pneumonia among Children Admitted in Dhulikhel Hospital - Sharma, Pradeep; Bhandari, Roshan; Poudel, Pranodan; Pandey, Ghanashyam; Paudyal, Richa (Journal of Nepal Health Research Council, 2023)
Background: Pneumonia is the commonest lung disease which is a major cause of mortality and morbidity in young children and is a common acute respiratory infection. The presentation varies among the cases. The study was done to know the risk factors, clinical profile, radiological findings, and short-term outcome of the admitted patients with pneumonia between six months to sixteen years at Dhulikhel Hospital.Methods: A hospital based observational prospective cross-sectional study done in 65 cases over the period of 17 months in children admitted with pneumonia at Pediatrics department of Dhulikhel Hospital. Socio-demographic variables, clinical profile, radiological profile, diagnosis, and short-term outcome were collected and analyzed using descriptive statistics. Results: Out of 65 patients, 76.9% cases were children between six months to five years. The most common clinical presentation was fever (98.5%) followed by cough (86.2%). Crepitation (78.5%) and subcostal retraction (29.2%) were common clinical findings. Disseminated intravascular coagulation, thrombocytopenia, sepsis, and right heart failure were associated with mortality. The requirement of mechanical ventilation, oxygenation, and inotrope support was more likely to have fatal outcome.Conclusions: Fever and cough were the most common clinical presentation and right middle zone consolidation was the most common finding in children admitted with pneumonia.Keywords: Cough; fever; pneumonia